Genome-Wide Identification and Expression Analysis of the Mango (Mangifera indica L.) SWEET Gene Family - Lirong Zhou; Xinyu Liu; Xiangchi Leng; Meng Zhang; Zhuanying Yang; Wentian Xu; Songbiao Wang; Hongxia Wu; Qingzhi Liang (Horticulturae)
The SWEET gene family is a group of genes with important functions in plants that is mainly involved in the transport and metabolism of carbohydrate substances. In this study, 32 mango (Mangifera indica L.) SWEET genes were screened and identified at the whole-genome level through bioinformatics methods. A systematic predictive analysis was conducted on their physicochemical properties, homology relationships, phylogenetic relationships, chromosomal locations, genomic structures, promoter cis-acting elements, and transcription factor regulatory networks. Meanwhile, the transcription levels of mango SWEET genes in different varieties and at different fruit development stages were also analyzed to obtain information about their functions. These results showed that 32 mango SWEET genes were unevenly distributed on 12 chromosomes. Phylogenetic analysis divided the SWEET proteins of mango, Arabidopsis thaliana (L.) Heynh., and Oryza sativa L. into four clades; in each clade, the mango SWEET proteins were more closely related to those of Arabidopsis. Four types of cis-acting elements were also found in the promoter regions of mango SWEET genes, including light-responsive elements, development-related elements, plant hormone-responsive elements, and stress-responsive elements. Interestingly, we found that the Misweet3 and Misweet10 genes showed strong expression in different mango varieties and at different fruit development stages, and they both belonged to the fourth Clade IV (G4) in the phylogenetic tree, indicating that they play a key role in the sugar accumulation process of mango. In this study, the upstream transcription factors of Misweet3, Misweet8, Misweet9, Misweet10, Misweet17, Misweet18, Misweet19, Misweet21, Misweet23, Misweet25, Misweet27, and Misweet31, those that had high expression levels in the transcriptome data, were predicted, and transcription factors such as ERF, NAC, WRKY, MYB, and C2H2 were screened. The results of this study provide a new way to further study the regulation of mango SWEET family genes on sugar accumulation, highlight their potential role in fruit quality improvement, and lay an important foundation for further study of mango SWEET function and enhance mango competitiveness in fruit market.